The Teacher's Challenges of the Implementation of Problem-Based Learning in Teaching English at SMKN 1 Toraja Utara - Pagampa, Yanti Inna; Siumarlata, Viktor; Arrang, Judith Ratu Tandi (Jurnal Studi Guru dan Pembelajaran, 2023)
The urgency of this research lies in addressing the practical challenges faced by teachers in implementing Project-Based Learning (PBL) within English instruction at SMKN 1 Toraja Utara, particularly under the Merdeka Belajar Curriculum. PBL is widely recognized for fostering critical thinking, collaboration, and authentic language use; however, its successful application requires adequate teacher preparation, resources, and supportive learning environments. This study adopts a qualitative approach, utilizing interviews, classroom observations, and document analysis to explore these challenges in depth. The findings indicate that teachers face substantial barriers, including insufficient formal training and limited understanding of PBL concepts, which hinder the design and facilitation of effective projects. Resource shortages, such as inadequate materials and budget constraints, further complicate implementation. Additionally, resistance from students and parents reduces motivation and acceptance of the approach. Time constraints emerge as a particularly critical obstacle, limiting opportunities for thorough planning, execution, and assessment of projects, despite the presence of some supportive facilities. Other notable issues involve difficulties in evaluating students’ problem-solving skills and managing diverse classroom dynamics to ensure equitable participation. These findings highlight the need for targeted professional development, improved resource allocation, and adaptive teaching strategies to align PBL with the vocational school context. While PBL presents significant educational benefits, addressing these constraints is essential for its effectiveness. The study recommends stronger institutional support and the integration of PBL-focused training into teacher development programs to enhance its sustainability and impact in vocational English education.